Telecommunications law indicators for comparative studies (TLICS) model : a hermeneutical approach - Aranha, Márcio Iório (2011)
This article proposes a model for identification of juridical variables to be used in ICT comparative analyses from the perspective of the information revolution category and dependence of economic development upon ICT: the Telecommunications Law Indicators for Comparative Studies (TLICS) model. The research question is: what is the correlation between traditional juridical theories on interpretation and the institutional variables used in comparative analyses of ICT regulatory models? The article is organized in three main parts. A review of the literature is performed in the first part, in which ICT comparative analyses are scrutinized to show how juridical variables are incorporated by them. The second part delves into the methodology, theory, and operational tool for the proposed model. The third part identifies dimensions and variables apt to depict the juridical framework of ICT comparative analyses. Betti‘s prescriptive hermeneutics and Hesse‘s hermeneutics are adopted as methodologies of approach, based upon the institutional theory of law (Santi Romano) and Schmitt‘s concept of institutional guarantees (institutionelle Garantien). As a main outcome, this article shows that juridical methodology, theory, and operative tools are important assets to assure the commensurability of institutional variables usually adopted by comparative research studies dealing with the relationship between development and ICT.